Exploring the bi-directional relationship of stock return and sustainability performance through the sustainability risk lens (case of Indonesia) - Sita Deliyana Firmialy; Sudarso Kaderi Wiryono; Yunieta Anny Nainggolan (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
Sustainability investing has been evolved significantly since the last decade. The inclusion of social, environmental, and economic dimension into the portfolio screening criteria is stated as an essential strategy to increase the firms' financial performance. However, previous empirical evidence has gained a mixed result on this issue (i.e. positive, negative, and insignificant). This study contributes to the discussion by offering result on the heterogeneous effect of sustainability performance to the stock return, specifically through the sustainability risk lens. Sustainability risk is related to firm sustainability concern of not being able to perform in a "sustainable manner", thus related directly to the inefficiency within the firms, as well as the firms' idiosyncratic risk. Uniqueness contribution of this study is by offering the analysis in a disaggregated ways (i.e. separately examines the relationship between each sustainability performance dimensions and stock return), within portfolio level. Using large size of cross-sectional data (more than 400 companies over two years span of time) covered all non-financial sectors listed in the Indonesia Stock Exchange (IDX), we are able to confirm the notion of heterogenous sustainability performance within Indonesian firms. We also found evidence on the positive direction of an increase of social and economic performance to stock return. Meanwhile, environmental sustainability performance shows the contrast direction.